The potential roles of herpesvirus and cytomegalovirus in the exacerbation of pemphigus vulgaris - Fariba Mohammadi (Mattioli1885, 2018)
Background: Among exogenous etiologies, the critical role of microbial agents such as herpesviruses (HSV1/2) and cytomegalovirus (CMV) in triggering and flaring autoimmune conditions such as pemphigus vulgaris (PV) has been recently discovered.